LINGUISTIC FEATURES OF NEWSPAPER HEADLINES ON ARTIFICIAL INTELLIGENCE IN THE ONLINE EDITIONS OF ITALIAN DAILY NEWSPAPERS (Živi jezici: Journal for Foreign Languages and Literatures, 2025)
In this paper, using the content analysis method, we examined the linguistic features of headlines about artificial intelligence extracted from the online editions of the most read Italian daily newspapers, Corriere della Sera and La Repubblica, published from January 2020 to September 2023. The research was conducted on a corpus of 864 newspaper headlines, which we analyzed from two perspectives – lexical and syntactic. Our aim was to, by analyzing the lexical composition of the newspaper headlines, present unadapted loanwords, terms, and onyms in our corpus, and to, within the syntactic analysis, explore the syntactic structures of the analyzed newspaper headlines. The research results indicated that in our corpus prevail anglicisms from the field of informatics, that among onyms the most frequent are names of tech companies, robots, chatbots, and virtual assistants, and that the majority of newspaper headlines were in the form of simple sentences.
Keywords: newspaper headlines; Italian daily online newspapers; artificial intelligence; Italian